TEACHING FACTORY AS PART OF EDUPRENEURSHIP: VOCATIONAL SCHOOL REVITALIZATION STRATEGY THROUGH TECHNOPARK - Ulfah Irani Z; Riyan Maulana; Syarifuddin; Rizaldi Akbar; Rita Zahara (CV Naskah Aceh, 2022)
Tekno Park is one of the strategies for developing edupreneurship and teaching factories in vocational high schools through cooperation and collaboration between vocational schools, government, universities, the world of industry and business, and other stakeholders. This research aims to describe how the development of teaching factories in Vocational High Schools through technopark innovation as well as the factors inhibiting the implementation of technoparks in Vocational Schools in Aceh Province. This research is a qualitative descriptive research conducted at three technoparks developed at vocational high schools in Aceh Province. The research subjects in this study were 30 respondents. Data was collected through observation instruments, documentation studies, interviews and questionnaires. Data analysis is carried out through data reduction, data display, and verification. The research results show that: (1) The implementation of technoparks at vocational high schools is carried out through the N-Tuple Helices model which involves government components, implementing vocational schools, other vocational schools, universities, vocational school alumni, the industrial and business world, and the community. The obstacles faced by vocational schools in developing technoparks include: (1) lack of productive teachers; (2) Technopark does not yet have patent rights and distribution permits for Technopark products; (3) obstruction of widespread marketing; (4) inadequate facilities and infrastructure; (5) limited working partners; (6) policies regarding the development of vocational schools and encouraging business and industry to partner with vocational schools; (7) budget.